2009
DOI: 10.1152/ajpheart.00893.2008
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor blockade combined with phosphodiesterase-5 inhibition increases right ventricular mitochondrial capacity in pulmonary arterial hypertension

Abstract: We determined the effects of single and combination treatment with Bosentan [an ET type A (ET A)/type B (ETB) receptor blocker] and Sildenafil (a PDE5 inhibitor) on RV function and oxidative metabolism in monocrotaline (MCT)-induced PAH. Fourteen days after MCT injection, male Wistar rats were orally treated for 10 days with Bosentan, Sildenafil, or both. RV catheterization and echocardiography showed that MCT clearly induced PAH. This was evidenced by increased RV systolic pressure, reduced cardiac output, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 53 publications
4
33
1
Order By: Relevance
“…In rats, in which PH is developed, right ventricular dilatation occurs whereas LVDD decreases. Mouchers et al has reported that in rats which PAH is formed LVDD was decreased; whereas the values have increased in sildenafi l group, but no increase in bosentan group (17). Moreover, similarly, our study also revealed smaller LVDD in the treatment groups when compared to SF group in PH developed rats.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In rats, in which PH is developed, right ventricular dilatation occurs whereas LVDD decreases. Mouchers et al has reported that in rats which PAH is formed LVDD was decreased; whereas the values have increased in sildenafi l group, but no increase in bosentan group (17). Moreover, similarly, our study also revealed smaller LVDD in the treatment groups when compared to SF group in PH developed rats.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to PAH development, treatment in PAH developed rats was studied in experimental models. Mouchers et al reported that RVDD has had a statistically signifi cant decrease in combined treatment group (17). RVDD was also decreased in sildenafi l group without a statistical signifi cance, whereas no decrease at all in bosentan group (17).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This could have affected the distribution of systemic perfusion, which has been reported to be altered in hypoxia [2]. Selective endothelin antagonist-mediated increases in nitric oxide availability [9] could improve mitochondrial capacity by a protein kinase Gmediated pathway, thereby improving myocardial and skeletal O 2 uptake [29,30]. Thus, sitaxsentan could also have affected the matching of convectional and diffusional oxygen transport systems, which have been modelled to occur at a lower Q in hypoxia [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as observed earlier, collagen fibers are expected to change as function of age or as wound healing progresses. It is also known that monocrotaline induced PH activates neurohumoral factors, which can also influence structural remodeling of the LV, in the absence of mechanical overload [1,23,27]. In addition, vice versa, the RV also shows severe fibrosis in the setting of systemic hypertension [4,39,47].…”
Section: Discussionmentioning
confidence: 99%